Metabolic changes in bladder cancer patients after urinary tract reconstruction using intestinal segments - Shamraeva, Daria; Vozianon, Sergiy (The Ukrainian Scientific Medical Youth Journal, 2024)
The goal is to evaluate the occurrence of short-term and long-term metabolic changes in patients with muscle-invasive bladder cancer (MIBC) after radical cystectomy (RCE) followed by orthotopic derivation of urine from segments of the small intestine or the formation of an ileal conduit with a "wet stoma" exit. During 2018-2020, the SI "Academician O.F. Vozianov Institute of Urology National Academy of Sciences of Ukraine" conducted examinations and treatments 22 patients diagnosed with MIBC at clinical stages T2aN0M0–T3bN0M0. In all cases, radical cystectomy and lymphadenectomy were performed using the laparoscopic method, but 8 (36.4%) patients had previously undergone open resection of the urinary bladder in other medical institutions. In five patients (22.7%), urine derivation was performed by the method of creating an ileal conduit according to Bricker. Eight (36.4%) patients underwent ileoneocystoplasty according to Studer, in nine (40.9%) patients, an orthotopic neocist was performed according to a modification of the 4 department of SI "Academician O.F.Vozianov Institute of Urology National Academy of Sciences of Ukraine", which consists in creating an orthotopic artificial bladder from a pre-resected segment of the ileum and anastomosing it with the proximal part of the urethra and the distal segments of the ureters, which differs from the commonly known method of ileonecystoplasty according to Studer in that, firstly, in the course of its implementation, the possibility of an instrumental intestinal suture is foreseen in the case of endoscopic variants of radical cystprostatectomy, and the length of the necessary ileal fragment was reduced to 50 cm. Second, a complete detubularization of the conventionally divided into right, middle and left segments of the intestine fragment: asymmetrically during its middle 5 cm with the formation of a cervical flap, and symmetrically - along the contramesenteric edge on the entire other length. Third, the medial edges of the right and left intestinal segments were first fixed to the upper edge of the middle segment. Fourth, after the creation of the eye of the neck of the future "neovesica", the upper and middle thirds of the lateral edge of the right and left intestinal segments were fastened together. Fifth, the original neck of the new intestinal bladder was formed by making vertical incisions of the pre-created eye of the reservoir neck at 12 and 6 o'clock of the conventional dial to expand its diameter to 1.0–1.5 cm, then step-by-step eversion and tubularization of the formed semicircles were performed on the urethral catheter by applying 3–5 knotted Vicryl 3.0 sutures and performing a neck duplication maneuver with two knotted sero-muscular sutures placed one above the other parallel to the axis of the neck with a step between the puncture and the puncture of the needle of 4 mm. Sixth, after the formation of the vesico-urethral anastomosis, the free edges of the cervical flap and the lower thirds of the lateral edge of the right and left intestinal segments were sutured, the oral and aboral intestinal openings were sealed, a cystostomy drainage was installed through the latter, and a reversible peritonization maneuver was performed. To compare the results of the study based on postoperative metabolic changes, all patients were divided into three groups: 1st group (5 patients) - with urine derivation according to Bricker, 2nd group (8 patients) - with ileoneocystoplasty according to Studer, 3rd group (9 patients) - which urine derivation was carried out orthotopically in a modification of the clinic (neocyst). To evaluate the advantages of our proposed method of creating an artificial bladder, the following indicators were evaluated: bladder volume, kidney concentration function (urine density), diarrhea after surgery, hypokalemia, the appearance of kidney stones, and kidney function was also evaluated according to the glomerular filtration rate (GFR). After the operation, the volume of the bladder or conduit changed depending on the group: it increased in patients of groups 2 and 3 (during the operation: group 2 – 380,0±1,4 ml, group 3 – 170,0±24,2 ml, after 6 months: 420,0±81,4 ml and 310,0±62,5 ml, respectively), but decreased in patients of group 1 (during surgery: 30,0±3,4 ml, after 6 months – 13,0±2,2 ml). Urine density indicators before the operation were within the normal range in all groups: 1st group – 1020,0±3,8; 2nd group – 1016,0±2,9; 3rd group – 1019,0±3,9. No changes in the concentration function were observed even after the operation according to Bricker (1015,0±5,0) one year after the operation. On the other hand, when performing orthotopic ileoneocystoplasty, an increase in the concentration function of the kidneys was noted (group 2 – 1050,0±7,3, group 3 – 1035,0±17,0). Diarrhea was observed in all patients after the start of feeding, but its duration was different. In patients with orthotopic methods, the duration of diarrhea was longer (group 1 – 3,0±1,2 days and was not observed 12 months after surgery, group 2 – 10,0±3,9 days, group 3 – 7,0±1,6 days). One year after the operation, two patients of group 2 and one of group 3 noted the presence of liquid stool once a day. In some patients of groups 2 and 3, a violation of the acid-alkaline balance was noted, which required correction: p/o HCO3− in group 2 – 19,0±1,6 mmol/l; in group 3 – 20,0±1,6 mmol/l. 1 year after surgery HCO3− in group 2 – 23,0±1,4 mmol/l; in group 3 – 24,0±1,6 mmol/l. Group 1 patients did not show changes in acid-base balance either in the early postoperative period or after one year (HCO3− immediately after surgery – 23,0±1,4 mmol/l, after 1 year – 24,0±1,4 mmol/l). In group 1, the concentration of K+ in serum immediately after surgery tended to decrease, but never exceeded the lower limit of normal (3,3±0,1 mmol/l) and there were no deviations one year after surgery (4,0±0,6 mmol/l). Among patients with orthotopic urine diversion, the most pronounced changes were observed in patients of group 2, where hypokalemia could reach 2,6±0,№ mmol/l immediately after surgery. Group 3 patients also showed a decrease in serum K+ after surgery (3,0±0,2 mmol/l), but these indicators were less pronounced and the patients were more likely to undergo medical correction. 1 year after the operation, a satisfactory concentration of K+ in blood serum was observed after conservative measures in groups 2 and 3 and amounted to 3,8±0,6 mmol/l and 4,3±0,9 mmol/l, respectively. Kidney calculi were found in two patients of group 1, one of them underwent remote shock wave lithotripsy 7 months after the operation, the second patient took citrate mixtures until the calculi completely regressed. In the second group there was 1 patient with kidney microliths who is under observation. No cases of urolithiasis were registered in group 3. A general decrease in GFR was found in all groups, but was more pronounced in patients of group 1 (GFR before surgery – 93,0±4,1 ml/min, 1 year after surgery – 35,0±6,9 ml/min). Of the patients in groups 2 and 3, the latter demonstrated the lowest rates of glomerular filtration reduction (108,0±13,4 ml/min before surgery and 93,0±14,5 ml/min after 1 year in patients of group 3 versus 95,0±3,8 ml/min before surgery and 84,0±12,8 ml/min after 1 year in patients of group 2). Modification of performing intracorporeal laparoscopic formation of an orthotopic neocyst according to the methodology of the 4th Department of Urology of the SI "Academician O.F.Vozianov Institute of Urology National Academy of Sciences of Ukraine" did not lead to the occurrence of uncontrolled metabolic disorders in the early and late postoperative periods in patients with MIBC and can be recommended for wider implementation in the clinical practice of urological and surgical departments of medical institutions of Ukraine.